PERGESERAN PARADIGMA BISNIS SEBAGAI UPAYA PREVENTIF PENEGAKAN ETIKA BISNIS DI INDONESIA - Pujiono Dewi Sulistianingsih (Masalah-Masalah Hukum, 2011)
Business practices has been a tendency to ignore business ethics in society. Violation of business ethics is motivated by the aim to gain as much as possible. This condition is obviously very detrimental to a sense of justice contained in the community This injustice will bring reaction from the community that is retaliation. With the vengeance of this community, will cause losses for the company itself, other firms, even more broadly detrimental to the nation and the State. Enforcement of business ethics must be executed with the firm. One theory that can be used to enforce business ethics is the theory of Chambliss and Seidman, where the enforcement of business ethics by using the theory of Chambliss and Seidman involves institution regulators and law enforcement agencies I Practitioners sanctions. With the existence of both institutions are expected to enforcement of business ethics can be optimized. Kata kunci: Etika, Bisnis, Penegakan Hukum